Use of Pentamidine As Secondary Prophylaxis to Prevent Visceral Leishmaniasis Relapse in HIV Infected Patients, the First Twelve Months of a Prospective Cohort Study. - Ermias Diro; Koert Ritmeijer; Marleen Boelaert; Fabiana Alves; Rezika Mohammed; Charles Abongomera; Raffaella Ravinetto; Maaike De Crop; Helina Fikre; Cherinet Adera; Robert Colebunders; Harry van Loen; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:Visceral leishmaniasis (VL) has become an important opportunistic infection in persons with HIV-infection in VL-endemic areas. The co-infection leads to profound immunosuppression and high rate of annual VL recurrence. This study assessed the effectiveness, safety and feasibility of monthly pentamidine infusions to prevent recurrence of VL in HIV co-infected patients. METHODS:A single-arm, open-label trial was conducted at two leishmaniasis treatment centers in northwest Ethiopia. HIV-infected patients with a VL episode were included after parasitological cure. Monthly infusions of 4 mg/kg pentamidine-isethionate diluted in normal-saline were started for 12 months. All received antiretroviral therapy (ART). Time-to-relapse or death was the primary end point. RESULTS:Seventy-four patients were included. The probability of relapse-free survival at 6 months and at 12 months was 79% and 71% respectively. Renal failure, a possible drug-related serious adverse event, occurred in two patients with severe pneumonia. Forty-one patients completed the regimen taking at least 11 of the 12 doses. Main reasons to discontinue were: 15 relapsed, five died and seven became lost to follow-up. More patients failed among those with a CD4+cell count ≤ 50 cells/μl, 5/7 (71.4%) than those with counts above 200 cells/μl, 2/12 (16.7%), (p = 0.005). CONCLUSION:Pentamidine secondary prophylaxis led to a 29% failure rate within one year, much lower than reported in historical controls (50%-100%). Patients with low CD4+cell counts are at increased risk of relapse despite effective initial VL treatment, ART and secondary prophylaxis. VL should be detected and treated early enough in patients with HIV infection before profound immune deficiency installs.